Utilization of Interactive E-Modules in Formation of Students’s Independent Characters in the Era of Pandemic - Ricu Sidiq; Najuah; Pristi Suhendro (CV. Inara, 2021)
During this covid-19 pandemic, students are required and expected to be independent in the activities of the learning process with the help of technology. This study aims to see how the use of interactive e-modules in increasing student learning independence. The research method used is a qualitative method with data collection techniques using literature studies from journals and previous research. Analysis of the literature review includes data collection, data reduction, data presentation, and concluding. The results showed that the use of interactive e-modules in increasing students learning independence proved to be effective because the form of presentation was arranged systematically and attractively which was a combination of several media such as audio, video, images, text, evaluation and was also equipped with instructions for use. Thus, interactive e-modules are very appropriate to be used in increasing student learning independence.